2008
DOI: 10.1177/0891988707311031
|View full text |Cite
|
Sign up to set email alerts
|

Computerized Maze Navigation and On-Road Performance by Drivers With Dementia

Abstract: This study examined the ability of computerized maze test performance to predict the road test performance of cognitively impaired and normal older drivers. The authors examined 133 older drivers, including 65 with probable Alzheimer disease, 23 with possible Alzheimer disease, and 45 control subjects without cognitive impairment. Subjects completed 5 computerized maze tasks employing a touch screen and pointer as well as a battery of standard neuropsychological tests. Parameters measured for mazes included er… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
83
0
2

Year Published

2008
2008
2017
2017

Publication Types

Select...
8
2

Relationship

2
8

Authors

Journals

citations
Cited by 81 publications
(87 citation statements)
references
References 36 publications
2
83
0
2
Order By: Relevance
“…For instance, two meta-analyses of the literature, one of persons with dementia (Reger et al, 2004) and one of older adults without a dementia diagnosis (Mathias and Lucas, 2009), provided support for the utility of tests of visuospatial abilities and visual attention, respectively, in predicting real-world driving ability. Tests of executive functions have also shown promise in predicting on-road (Ott et al, 2008;Whelihan et al, 2005) and crash involvement (Daigneault et al, 2002), although executive functioning has not been examined as extensively as other neurocognitive domains. Nevertheless, neuropsychological test scores do not correlate entirely with functional outcomes (Sadek and van Gorp, 2010), and current investigations attempt to conclude the most effective assessment methods for detecting driving deficits (Morgan and Heaton, 2009).…”
Section: Introductionmentioning
confidence: 99%
“…For instance, two meta-analyses of the literature, one of persons with dementia (Reger et al, 2004) and one of older adults without a dementia diagnosis (Mathias and Lucas, 2009), provided support for the utility of tests of visuospatial abilities and visual attention, respectively, in predicting real-world driving ability. Tests of executive functions have also shown promise in predicting on-road (Ott et al, 2008;Whelihan et al, 2005) and crash involvement (Daigneault et al, 2002), although executive functioning has not been examined as extensively as other neurocognitive domains. Nevertheless, neuropsychological test scores do not correlate entirely with functional outcomes (Sadek and van Gorp, 2010), and current investigations attempt to conclude the most effective assessment methods for detecting driving deficits (Morgan and Heaton, 2009).…”
Section: Introductionmentioning
confidence: 99%
“…Recent reviews have found that similar tests of visuospatial skill, psychomotor speed, and attention are predictive of driving ability in stroke survivors (Devos et al, 2011;Marshall et al, 2007), providing convergent validation for our approach. Furthermore, studies in older adults with cognitive impairment have reported utility for these types of tests (Ott et al, in press) and for both handdrawn (Snellgrove, 2005) and computerized mazes (Ott et al, 2008;Staplin, Gish, Lococo, Joyce, & Sifrit, 2013). Therefore, further development of such tests is indicated.…”
Section: Discussionmentioning
confidence: 99%
“…However, the majority of these articles were related to medical fields, including studies of occupational therapist driver assessors or associations between driving and illnesses such as dementia; stroke; Parkinson's disease; visual impairment; neurological conditions; orthopaedic issues; sleep problems; attention deficit hyperactivity disorder (ADHD); autism spectrum disorder (ASD); Down's syndrome; and the effect of drugs, medications and alcohol. [20][21][22][23][24][25][26][27][28] The subject population was often composed of older drivers, with the articles focusing on their fitness to drive. Critically, even if PDIs were involved in some articles, they were not the main subjects but were instead contributors, for instance in upholding the research design or its validity and reliability.…”
Section: Methodsmentioning
confidence: 99%